Affection versus Solidarity in the Phatic Strategies of Men and Women: A BNC64 Corpus Analysis - Rizky Ismail J; Annisa Nurul Firdausi (Ruang Kata, 2026)
Language as a communication mode reveals certain patterns to both our conscious and unconscious minds which help to index people as a part of certain groups such as determining speech in gender study. Gender study is now commonly grouped into men’s and women’s speeches. Men’s and Women’s sociocultural behaviors are different and can be reflected through their speech. This study aims to analyze the phatic expressions used by two genders: men and women. This study applied a qualitative method with thematic analysis to discover the pattern of gender speech and used quantified data to determine the frequency. The data were collected using BNC64 and the frequency distribution was also taken from the corpus. The findings show that women speak in a more prolonged speech to keep the communication going compared to men who are still using it but in shorter ways than women. The findings show phatic speech in the form of expressing greetings, invitations, comments, and condolences. These results indicate that women are speaking in a more caring and friendly way than men. Therefore, phatic expressions can be used for further study to analyze the characteristics and stereotypes in men’s and women’s conversations in a certain community